Sosialisasi Meningkatkan Semangat Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri 36 Bengkulu Tengah - Fadilah Fadilah; Rosdiana Dwiyanti; Malika Diah Puspita Sari; Tiwi Tamara; Dopa Lista; Sisi Anoli Putri; Tri Agina Sapira; Anita Anggraeni; Sumarta Dinata; Abdul Bashit Al Fikri; Candra Pratama (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
The limited level of public education and the low level of education and skills in the field of Islam are quite complex problems in the development process. The pursuit of knowledge is very important because knowledge is a means that everyone uses to achieve prosperity in this world and the hereafter. This lack of understanding of the teachings of the Islamic religion is very embarrassing because Islamic religious education is very important. On this occasion, we, students of KKN UIN FAS group 18, will provide an understanding of Islamic religious education to the children of State Elementary School 36, Central Bengkulu. The method of implementing community service that we carry out is a qualitative descriptive method. From the activities that have been carried out it can be confirmed that studying Islam in elementary schools has a lot of importance for children's development. The following are several reasons why Islamic religious education is important at the elementary school level, Character Formation, Understanding of Ethics and Morals, Introduction to Spiritual Values, Knowledge of Worship, Prevention from Negative Influences, Strengthening Islamic Identity, and Preparing a Generation with Noble Characters. Based on the implementation of activities and learning during the activities, it is known that socialization related to increasing enthusiasm for learning Islamic religious education at SDN 36 Central Bengkulu City has influenced students and teachers. The real impact is expanding understanding of Islamic religious knowledge through improving learning methods and utilizing the latest technological advances. Apart from that, as activity participants, students can gain insight into the importance of studying Islam so that they are more easily motivated.